Calcium supplementation and risk of cardiovascular disease - Nuti, Ranuccio (CIC Edizioni Internazionali, 2012)
With the outcome to demonstrate the efficacy of calcium to prevent the incidence of fractures many randomized controlled trials have been performed in the past two decades, with conflicting results. A RR of 0.86 for non-vertebral fractures and a RR of 0.91 for hip fractures on eight trials were demonstrated. Calcium supplementation is considered particularly important when baseline calcium intake is low. More recently WHI CaD Study indicated that calcium supplements with or without vitamin D represent a factor risk for cardiovascular events. On the other hand the beneficial effect of a correct calcium intake in attaining and maintaining bone mass across the life is largely demonstrated. There is an urgent need for more research to gain insight into the mechanisms of the adverse vascular effect of calcium. Moreover, more extensive data about the incidence of cardiovascular adverse events coming from randomized controlled intervention trials in osteoporosis, in which calcium plus Vitamin D were utilized, might be achieved.